Deubiquitinase OTULIN dampens RIG-I-dependent antiviral signaling by removing linear ubiquitination from TRAF6 - Rong-Chun Tang; Zhiheng Tang; Shuang-Shuang Yu; Ao Zhang; Shijin Geng; Hengxiang Yu; Yunxuan Zhou; Lan Zhang; Xiaoyun Liu; Jun Zhang (Proceedings of the National Academy of Sciences, 2026)
Linear ubiquitination and deubiquitination represent critical regulatory mechanisms in inflammation and cell death, yet their roles in RIG-I-like receptor (RLR)-dependent signaling remain unclear. Here, we identified OTU deubiquitinase with linear linkage specificity (OTULIN) as a negative regulator of RIG-I-dependent type I IFN (IFN-I) signaling. Overexpression of OTULIN markedly attenuated NF-κB and IFNβ reporter activation triggered by RNA viruses or synthetic analogs, suppressed downstream gene expression, impaired IFN-I production, and diminished phosphorylation of IκBα, TBK1, and IRF3, thereby facilitating viral replication. Conversely, knockout of OTULIN in HeLa and iBMDM cells enhanced these antiviral signaling events and restricted viral replication. Critically, reintroducing OTULIN into OTULIN -KO cells via lentiviral transduction reversed this enhanced phenotype, restoring the suppression of IFN-I signaling. Mechanistically, RNA virus infection induced linear ubiquitination of TRAF6 at K104, K142, and K371. LUBAC promoted antiviral innate immune signaling by enhancing the linear ubiquitination of TRAF6, which was antagonized by OTULIN. Notably, the linear ubiquitination of TRAF6 facilitated its K63-linked ubiquitination and strengthened its association with MAVS, amplifying the antiviral response. Furthermore, Otulin +/− mice exhibited enhanced antiviral immunity and more efficient viral clearance than wild-type littermates. Collectively, these findings unveil a regulatory role of OTULIN in attenuating RIG-I-dependent IFN-I signaling through removal of linear ubiquitination from TRAF6, highlighting the essential equilibrium between linear ubiquitination and deubiquitination in antiviral innate immunity and immune homeostasis.